In Hospital Clinical Outcome of Percutaneous Coronary Intervention (PCI) Result of 150 Cases - Uddin, Jamal; Ali, Mahboob; Choudhury, AHK; Majumber, AAS; Hossain, N; islam, Khondker Q; Raisuddin, M; Rahman, F; Salam, Muhammad Abdus; Khan, Kaiser Nasrulla; Marufuzzaman, SK; Hasan, Kazi Abul; et al. (Nepalese Heart Journal, 2004)
This is a ongoing study done in National Institute of Cardiovascular Diseases (NICVD), Dhaka, Bangladesh during the period May 2002 to June 2003. Total number of study population was 150 with male 135 & female 15. Indication of percutaneous coronary intervention (PCI) was Unstable angina with no prior myocardial infarction 60 cases. Myocardial infarction (MI) inferior with postmyocardial infarction angina 40 cases & MI anterior with post MI angina 50 cases. The risk factors were Hypertension (HTN) in 72 cases (48%), smoking in 90 cases (60%), Diabetes Mellitus (DM) in 50 cases (33.33%), Positive family history for ischemic heart disease (IHD) in 40 cases (26.66%) and Dyslipidemia 35 cases (23.32%), Total number of target coronary arteries were 190 of which 184 lesions treated. Distribution of 184 lesions were left anterior descending coronary artery (LAD) 91 (Proximal LAD 40, mid LAD 40, distal LAD 11), Right coronary artery (RCA) 60 (Proximal 15, mid RCA 40, distal RCA 05), Left circumflex coronary artery (LCX) 26 (Proximal LCX 05, mid LCX 15, distal LOX 04, LCX PD 02), Diagonal 02, Obtuse marginal (OM) 04, Ramus intermedius 02.